2012
DOI: 10.1186/1471-2296-13-42
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among caregivers of patients with schizophrenia: a cross-cultural comparison of Chilean and French families

Abstract: BackgroundTo our knowledge, no study has examined quality of life (QoL) among caregivers of individuals with schizophrenia between a developing and a developed country. The aim of this study was to assess QoL of the caregivers of individuals with schizophrenia in two countries characterized by different social, economic and cultural conditions, namely Chile and France.MethodsData were collected from public mental health outpatient services in Arica (Chile), and in Marseille (France). QoL was measured with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 24 publications
3
51
4
2
Order By: Relevance
“…Relatives have thus become the most important caregivers for adults with major psychiatric disorders and supply the patient with care and support [6]. Several studies have explored the impact of caring psychiatric patients [2,[7][8][9][10] and have reported that caring for a patient with schizophrenia resulted in a significant and substantial burden [11,12], lower quality of life levels [13,14], restricted roles and activities and increased psychosomatic, anxious or depressive symptoms [15,16]. In addition, caregivers' negative experience may affect their ability to care for the patients [4,17].…”
Section: Abstract: Burden • Caregivers • Coping • Family • Perceptionmentioning
confidence: 99%
“…Relatives have thus become the most important caregivers for adults with major psychiatric disorders and supply the patient with care and support [6]. Several studies have explored the impact of caring psychiatric patients [2,[7][8][9][10] and have reported that caring for a patient with schizophrenia resulted in a significant and substantial burden [11,12], lower quality of life levels [13,14], restricted roles and activities and increased psychosomatic, anxious or depressive symptoms [15,16]. In addition, caregivers' negative experience may affect their ability to care for the patients [4,17].…”
Section: Abstract: Burden • Caregivers • Coping • Family • Perceptionmentioning
confidence: 99%
“…Restoration of patient functioning in family and social roles, lack of spare time, and economic burden are some of the factors causing the distress, which can be subjects for future interventions [3]. Boyer et al [4] suggest interventions focusing on coping strategies, the improvement of the social network, stigma reduction and the development of personal strength to improve caregivers' QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver dapat mengalami penurunan kualitas hidup dalam merawat klien skizofrenia. Penelitian Boyer et al (2012) Rendahnya tingkat pengetahuan yang terjadi dapat dipengaruhi oleh tingkat pendidikan caregiver yang juga berada dalam ketgori rendah yaitu rata-rata SMP, dan usia caregiver yang diatas 40 tahun serta yang rata-rata caregiver adalah perempuan.…”
Section: Pendahuluanunclassified
“…Hasil ini, sejalan dengan penelitian Boyer et al (2012) meyatakan bahwa rasa tanggung jawab yang dimiliki oleh caregiver merupakan srategi yang diguankan oleh caregiver dalam merawat klien skizofrenia. Strategi ini sebagian besar digunakan oleh caregiver yang berperan sebagai seorang ibu.…”
Section: Strategi Koping Yang Digunakanunclassified